Legal agglomeration and undetermined death: prision economy and COVID-19 - Fernandes, Ionara dos Santos (Argumentum, 2021)
The text aims to problematize the impacts of some state measures to combat the pandemic of the new coronavirus in the Brazilian prison system. The dialogue is based on contemporary thematic literature, collective reflections and documents presented by the Rio de Janeiro State Mechanism for Preventing and Combating Torture. The data reveal that the strategies adopted by the bodies that make up the criminal justice system and the prison system enhance the proliferation of COVID-19 among inmates, promoting the state's death policy and strengthening profitable private actions fundamental to the reproduction of neoliberalism.